Assessment of functional defecation disorders using anorectal manometry - Seong, Moo-Kyung (Ann Surg Treat Res, 2018)
PURPOSE: The aim was to evaluate the discriminating accuracy of anorectal manometry (ARM) between nonconstipated (NC) subjects and functionally constipated (FC) subjects, and between FC subjects with and without functional defecation disorder (FDD). METHODS: Among female patients who visited anorectal physiology unit, those who could be grouped to following categories were included; FC group with FDD (+FDD subgroup), or without FDD (−FDD subgroup) and NC group. ARM was performed and interpreted not only with absolute pressure values, but also pattern classification and quantification of pressure changes in the rectum and anus during attempted defecation. RESULTS: There were 76 subjects in NC group and 75 in FC group. Among FC group, 63 subjects were in −FDD subgroup and 12 in +FDD subgroup. In pattern classification of pressure changes, type 0, as ‘normal’ response, was only slightly more prevalent in NC group than in FC group. When all ‘abnormal’ types (types 1–5) were considered together as positive findings, the sensitivity and specificity of pattern classification in diagnosing FC among all subjects were 89.3% and 22.7%. Those values in diagnosing FDD among FC group were 91.7% and 11.1%. Manometric defecation index (MDI) as a quantification parameter was significantly different between −FDD and +FDD subgroups. Other conventional absolute pressures were mostly comparable between the groups. CONCLUSION: Among all parameters of ARM, MDI was useful to diagnose FDD in FC patients. Other parameters including the pattern classification were questionable in their ability to diagnose FDD.